Flexible, Functional, and Familiar: Characteristics of SARS-CoV-2 Spike Protein Evolution - Saputri, Dianita S.; Li, Songling; van Eerden, Floris J.; Rozewicki, John; Xu, Zichang; Ismanto, Hendra S.; Davila, Ana; Teraguchi, Shunsuke; Katoh, Kazutaka; Standley, Daron M. (Frontiers in Microbiology, 2020)
The SARS-CoV-2 S protein is a major point of interaction between the virus and the human immune system. As a consequence, the S protein is not a static target but undergoes rapid molecular evolution. In order to more fully understand the selection pressure during evolution, we examined residue positions in the S protein that vary greatly across closely-related viruses but are conserved in the subset of viruses that infect humans. These "evolutionarily important" residues were not distributed evenly across the S protein, but were concentrated in two domains: The N-terminal domain and the receptor-binding domain, both of which play a role in host cell binding in a number of related viruses. In addition to being localized in these two domains, evolutionary importance correlated with structural flexibility and inversely correlated with distance from known or predicted host receptor binding residues. Finally, we observed a bias in the composition of the amino acids that make up such residues toward more human-like rather than virus-like sequence motifs.